Enterprise JavaBeans 3.0 - Poo, Danny C.C.
This fifth edition, written by Bill Burke and Richard Monson-Haefel, has been updated to capture the very latest need-to-know Java technologies in the same award-winning fashion that drove the success of the previous four strong-selling editions. Bill Burke, Chief Architect at JBoss, Inc., represents the company on the EJB 3.0 and Java EE 5 specification committees. Richard Monson-Haefel is one of the world's leading experts on Enterprise Java